Increasing Communication Literacy at Public Elementary School 05 Pemulutan - Nopriani, Elza; Fauzi , Leo Ferdian; Bastian; Misnawati, Desy (PT FORMOSA CENDEKIA GLOBAL, 2024)
Literacy is a symbol, system, and sound structure that conveys meaning, representing a fundamental competency encompassing four language skill listening, speaking, reading, and writing. One key element in education is communication literacy, which is an individual’s ability to context. This research aims to raise awareness among elementary school students about the importance of communication literacy at SD Negeri 05 Pemulutan. The research employs two methodes 1) Conventional and 2) Question and Answer. The conventional method assesses the extent of student’s compherension through interactive questioning. The results indicate that concrete steps have been taken to improve student’s communications literacy, previously at a low level. These efforts have assisted students in increasing their interest in reading and writing, as well as enhancing their abilities to use information and communication technology. This research contributes insight into how to enhance communication literacy at the elementary school level by demonstrating the effectiveness of specific teaching strategies and involving various stakeholers.